Práticas e possibilidades na Avenida Paulista - Monferdini, Juliana Aoun (2013)
Reflection on the quality of public spaces on Avenida Paulista, based on direct observation of the use of these spaces by the population. Record of the avenue daily episodes, recognized as extremely informative situations, able to point to these spaces plural meanings and unsuspected potential for its improvement by urban redesigning.